Hubungan harapan pemenuhandengan motivasi untuk menikah pada lanjut usia kebutuhan seksual - Suhartanto Purwanto, Ibrahim Rahmat (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Maslow said one of basic human needs was sexual that must be needed because of its direct relation with homeostasis. The sexual need was felt by the elderly in the intitution for elderly or community. Marriage was good a policy to meet sexual need for elderly. Marriage has not happened yet in the institution for elderly at Yogyakarta unit Budhi Luhur. Objective: to know the relation between expectation of accomplishment of sexual requirement and the motivation to marry of elderly in the institution for elderly at Yogyakarta Unit Budhi Luhur. Method: This study was analytic descriptive research type with cross-sectional approach. The study sample was elderly in the institution for elderly at Yogyakarta Unit Budhi Luhur not having a spouse, still able to communicate verbally and or in writing; and willing to become sample. Instrument used consisted of questionnaire concerning expectation of accomplishment of sexual requirement of male and female elder people. Focus Group discussion (FGD) was conducted twice, of a male and female elderly group. The product moment correlation coefficient statistic was used to test the result. Result: There are no relation between expectation of accomplishment of requirement of man sexual and the motivation to marry male elderly, with r= 0,180 and p= 0,448 (p›0,05). There was no relation between expectation of accomplishment of requirement with the motivation to marry female elderly, with r= -0,231 and p= 0,256 (p>0,05). Conclusion: There are no relations between expectations of accomplishment of sexual requirement and the motivation to marry in the isntitution elderly at Yogyakarta Unit Budhi Luhur. Keywords expectation, sexual requirement, motivate, nuptials